Pengembangan Media Pembelajaran PowerPoint Interaktif Berbasis Inkuiri Terbimbing pada Materi Larutan Elektrolit dan Nonelektrolit Kelas X SMA/MA - Siti Aisyah Nasution; Syamsi Aini (Universitas Negeri Padang, 2021)
Electrolyte and nonelectrolyte solutions are one of the materials in SMA/MA class X chemistry. The materials of electrolyte and nonelectrolyte solutions can be understood well through their macroscopic, submicroscopic, and symbolic representations. This study aims to develop interactive PowerPoint learning media based on guided inquiry on electrolyte and nonelectrolyte solution material for class X SMA/MA which is in accordance with the characteristics of the material and the demands of the 2013 curriculum. (define, design, develop, and disseminate). This research is limited to the develop stage. Testing the validity and practicality of interactive PowerPoint learning media based on guided inquiry on electrolyte and nonelectrolyte solution material using an instrument in the form of a questionnaire. The subjects of the validity test of this interactive PowerPoint learning media were three chemistry department lecturers and two MAN chemistry teachers. The practicality test subjects of this interactive PowerPoint learning media were two MAN 5 chemistry teachers and twenty MAN 5 Mandailing Natal students. The data obtained from the questionnaire were processed using the kappa moment to obtain the k value of each validity and practicality test item. The interactive learning media of electrolyte and nonelectrolyte solutions produced in this study had a validity k value of 0.86 and practicality by teachers and students obtaining k values of 0.895 and 0.89, with very high criteria of validity and practicality. Larutan elektrolit dan nonelektrolit merupakan salah satu materi dalam kimia SMA/MA kelas X. Materi larutan elektrolit dan nonelektrolit dapat dimengerti dengan baik melalui representasi makroskopik, submikroskopik, dan simboliknya. Penelitian ini bertujuan untuk mengembangkan media pembelajaran PowerPoint interaktif berbasis inkuiri terbimbing pada materi larutan elektrolit dan nonelektrolit kelas X SMA/MA yang sesuai dengan karakteristik materi dan tuntutan kurikulum 2013. Penelitian yang dilakukan termasuk jenis penelitian pengembangan (research and development) dengan model 4-D (define, design, develop, dan disseminate). Penelitian ini dibatasi sampai tahap develop. Pengujian validitas dan praktikalitas media pembelajaran PowerPoint interaktif berbasis inkuiri terbimbing pada materi larutan elektrolit dan nonelektrolit menggunakan instrumen berupa angket. Subjek uji validitas media pembelajara PowerPoint interaktif ini adalah tiga orang dosen jurusan kimia dan dua orang guru kimia MAN. Subjek uji praktikalitas media pembelajaran PowerPoint interaktif ini adalah dua orang guru kimia MAN 5 dan dua puluh orang siswa MAN 5 Mandailing Natal. Data yang dihasilakan dari angket diolah memakai momen kappa untuk memperoleh nilai k setiap item uji validitas dan praktikalitas. Media pembelajaran interaktif larutan elektrolit dan nonelektrolit yang dihasilkan pada penelitian ini memiliki nilai k kevalidan 0,86 dan kepraktisan oleh guru dan siswa memperoleh nilai k 0.895 dan 0.89, dengan kriteria kevalidan dan kepraktisan sangat tinggi.